Happiness of Economists - Lars P. Feld; Sarah Necker; Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the importance of economists' professional situation toward their life satisfaction based on a unique survey of mostly academic economists. On average, economists report to be highly happy with life. Satisfaction is positively related to spending more time on doing research. The lack of a tenured position decreases satisfaction. However, the extent to which the uncertainty created by the tenure system affects satisfaction varies with the contract terms. The effect is stronger if the contract expires in the near future or cannot be extended. Publication success has no effect if it is controlled for academic rank and the contract duration. The finding suggests that publications are rather a means to an end, e.g., to acquire a tenured position. While the perceived level of external pressure also has no impact, the perceived change of pressure in recent years is positively related to economists' life satisfaction. An explanation is that economists have accepted a high level of pressure when entering academia but are not willing to cope with the recent increase.
Keywords: I31; A11; J28; 330; happiness; academic labor market; extrinsic and intrinsic motivation; publish or perish